2017
DOI: 10.17135/jdhs.2017.17.6.508
|View full text |Cite
|
Sign up to set email alerts
|

Effective Management Interval Focused on Professional Mechanical Tooth Cleaning

Abstract: This study was conducted to investigate the optimal management interval in 33 healthy adults by observing changes in oral health on the basis of the plaque control index and gingival index. When plaque control score was compared according to the period, it was found that oral hygiene management was the best in the fourth visit (p<0.05). Improved oral hygiene status was observed during the 3-and 6-month follow-up (p<0.05). Regarding gingival index, the fourth visit showed the healthiest gingival status (p<0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Therefore, in addition to the phase difference microscope used to recognize the importance of oral care, as suggested by Mendoza et al [8], methods such as lowering the fee and making patients pay in advance so that they have regular visiting habits are considered. In addition, a method of motivating practice by informing the results of the evaluation of the oral hygiene status of patients mentioned in the author's study [4] through text is also an issue to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in addition to the phase difference microscope used to recognize the importance of oral care, as suggested by Mendoza et al [8], methods such as lowering the fee and making patients pay in advance so that they have regular visiting habits are considered. In addition, a method of motivating practice by informing the results of the evaluation of the oral hygiene status of patients mentioned in the author's study [4] through text is also an issue to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, as the prevalence of implants increases in the dental community, interest in prevention-oriented management programs is increasing so that patients can recognize the need for dental plaque control and cultivate the ability to do oral management on their own. Looking at previous studies related to this, researcher Park and researcher Han [2] reported the effect of reduction of Peri-implantitis through professional tooth cleaning and plaque control, and Ma [3] reported that it should continue to be performed at regular intervals depending on the oral condition of patients through a preventive management program using professional mechanical tooth washing (PMTC) [4] . In addition, in a previous paper, the author reported the effectiveness of the PMTC-centered prevention management program and the importance of re-education every three months was reported, and it has been reported that when applying a PMTC-centered preventive management program to patients undergoing implant procedures, the learning period that can induce differentiation of oral health education content and oral hygiene management attitude should be considered [5].…”
Section: Introductionmentioning
confidence: 99%